PERAN PENTING ILMU TEKNOLOGI CCTV DALAM PEMBUKTIAN ELEKTRONIK BERDASARKAN UNDANG-UNDANG ITE - Yanti Kirana (LPPM STIH Awang Long, 2025)
Various aspects of human life today, including technology, are developing rapidly. Nowadays, it seems difficult to separate human life from technology, which has even become a necessity. Initially, technology was part of or dependent on science, but now it can also depend on science. One example is the development of science and technology related to Closed Circuit Television (CCTV), which plays a central role in electronic evidence under the Electronic Information and Transactions Law (UU ITE). Social and moral life is influenced by the technological devices we value. They enhance people's worldviews, social practices, organizations, values, and lifestyles. Today, it is difficult to be truly active in technological decisions when technological devices are often forced upon us, forcing us to do many things. While this technological development has a positive impact, it also has a negative impact, as it can hinder direct interaction between people, as people already interact so much indirectly and everyone is dependent on technology, especially CCTV. CCTV recordings are recognized as valid electronic evidence under Indonesian law, provided they meet certain procedural requirements. CCTV footage can be used in criminal proceedings as evidence, and its validity is regulated in Article 5 paragraphs (1) and (2) and Article 44 of the ITE Law. However, this journal also reviews the requirements, for example, the need to be linked to other evidence to become strong indicative evidence, or the need for expert testimony to ensure the authenticity of data if transferred via physical media such as flash drives. Technological developments are occurring at an extraordinary pace, undeniably dominating every aspect of life. This study explains the important role of CCTV technology in electronic evidence based on the ITE Law.